New wine in old bottles or old wine in new bottles? - Tittenbrun, Jacek (Studia Krytyczne/Critical Studies, 2019)
The present paper offers a critical analysis of what its authors call a new approach to social class. The analytical framework concerned is based on a large BBC-sponsored Internet survey and co-coauthored by a team of researchers led by Mike Savage. In theoretical terms, the most relevant observation to be made regarding the appproach under examination is its total dependence upon Pierre Bourdieu's concepts and ideas. This concerns first of all his theory of multiple 'capitals', two of which, e.e. social and cultural have been singled out by the exponents of the framework analysed in the paper as the building blocks of their own class theory. In other publications of the present author it has been shown that the purported Bourdesian 'capitals' are not any capitals at all, that they constitute misnomers, or even oxymorons. The consequences of this theoretical misunderstanding, to say the least, are as devastating in the case of Savage et al. as in the case of French thinker. The typology of social classes built upon such shaky grounds is found wanting in many respects; inter alia, such concepts as the middle class and the precariat are being criticised in more detail. Overall, the authors' shameless self-adevertising campaign, their analytic framework contains scarcely any new insights or ideas and mirrors other people's errors and failings instead.